Untersuchungen zur Herstellung von funktionsoptimierten Bauteilen im partiellen Presshärtprozess mittels lokal unterschiedlich temperierter Werkzeuge - Svec, Thomas (2015)
The objective of this work is to manufacture functionally optimized components with locally adjusted mechanical properties in partial hot stamping process by controlling the cooling conditions using locally different heated tools. The influence of forming process at elevated temperatures and the relationships between material and process parameters on the thermal processes and the resulting mechanical properties are investigated and characteristic values are verified by numerical calculation